Екологічний аудит й оцінка впливу сільськогосподарської діяльності на стан природних ресурсів агросфери - Кочерга, М.М. (Економіка природокористування і охорони довкілля, 2013)
Обґрунтовано методичні основи еколого-економічної оцінки впливу сільськогосподарської діяльності на стан природних ресурсів агросфери з метою створення умов для збалансованого розвитку агроекосистем. Запропоновано схему здійснення даної оцінки при проведенні екологічного аудиту об’єктів у сільському господарстві. Developed Methodical bases of ecological-economic evaluation of the impact of agricultural activities on the state of natural resources to create the conditions for sustainable development of agro-ecosystems. Proposed a scheme of this assessment at carrying out environmental audit of objects in agriculture. The principles of environmental and economic assessment of the impact of agriculture on natural resources agrosphere proposed to reduce to determine the difference between the environmental and economic potential of the ecosystem before the economic activity and after certain stages.